The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1155/2016/7164623
|View full text |Cite
|
Sign up to set email alerts
|

A Matched Case-Control Study of Risk Factors for Breast Cancer Risk in Vietnam

Abstract: Background. Vietnam has a low age-standardized incidence of breast cancer, but the incidence is rising rapidly with economic development. We report data from a matched case-control study of risk factors for breast cancer in the largest cancer hospital in Vietnam. Methods. 492 incident breast cancer cases unselected for family history or age at diagnosis and 1306 control women age 25–75 were recruited from the National Cancer Hospital (BVK), Hanoi. Structured interviews were conducted and pathology data was cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
31
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 27 publications
3
31
2
Order By: Relevance
“…In this study the age incidence of cancer was relatively early and high in comparison with other study which has been done on 286 patients in Iran; they found the incidence of cancer was higher in older age women age (Account et al, 2002) and other study from Canada (Nguyen et al, 2014).…”
Section: Resultscontrasting
confidence: 39%
“…In this study the age incidence of cancer was relatively early and high in comparison with other study which has been done on 286 patients in Iran; they found the incidence of cancer was higher in older age women age (Account et al, 2002) and other study from Canada (Nguyen et al, 2014).…”
Section: Resultscontrasting
confidence: 39%
“…Later diagnosis was also predominant in another study where 64.2% of 4715 new breast cancer cases diagnosed in five provinces were found at Stage III or stage IV [29]. Two further papers, including one retrospective study on stages of diagnosis across five hospitals in 2009, found that 49.5% of the women were diagnosed with Stage III or IV breast cancer [15], while 67.7% in the second study were diagnosed at Stage II [30]. …”
Section: Resultsmentioning
confidence: 99%
“…Reviewing process was held to select 10 studies related to the duration of oral contraceptive application with breast cancer risk in Southeast Asian women with a total 28,776 samples patients (Table 1) [13,[16][17][18][19][20][21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%
“…Subgroup analysis for oral contraceptive use and breast cancer risk in Southeast Asia (Table 2). Ten studies assessing oral contraceptive application and breast cancer risk, seven were case-control studies [13,[16][17][18]21,22] with Pooled Odds Ratio (POR) 1.52 (1.06-2.18), heterogeneity test in these studies (P heterogeneity = <0.001; I 2 = 90%) resulted in various heterogeneous research on breast cancer risk, and three were cohort studies [19,20] with POR 1.34 (0.98-1.84), heterogeneity test in these studies (P heterogeneity = 0.28; I 2 = 21%) resulted in a variety of homogeneous research on the breast cancer risk.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation